( r 1 + 2 9 ) ( r 2 + 2 9 ) ( r 3 + 2 9 ) ( r 4 + 2 9 )
Let r 1 , r 2 , … , r 4 be the roots of x 4 + 7 x 3 − 2 x 2 + 3 x + 1 7
Find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y=x+29 and substitute (y-29) for x in the equation. We get
(
y
−
2
9
)
4
+
7
∗
(
y
−
2
9
)
3
−
2
∗
(
y
−
2
9
)
2
+
3
∗
(
y
−
2
9
)
+
1
7
=
0
.
∴
a
4
∗
y
4
+
a
3
∗
y
3
+
a
2
∗
y
2
+
a
1
∗
y
+
{
(
−
2
9
)
4
+
7
∗
(
−
2
9
)
3
−
2
∗
(
−
2
9
)
2
+
3
∗
(
−
2
9
)
+
1
7
}
.
⟹
a
4
∗
y
4
+
.
.
.
+
a
1
∗
y
+
5
3
4
8
0
6
.
By Vieta the product of each root of y is the constant term 534806.
But y=x+29. So roots of y are roots of x plus 29. So 534806 is the required product.
Great job on that!
Problem Loading...
Note Loading...
Set Loading...
x 4 + 7 x 3 − 2 x 2 + 3 x + 1 7 = ( x − r 1 ) ( x − r 2 ) ( x − r 3 ) ( x − r 4 ) ⇒ ( 2 9 + r 1 ) ( 2 9 + r 2 ) ( 2 9 + r 3 ) ( 2 9 + r 4 ) = ( − 1 ) 4 ⋅ ( − 2 9 − r 1 ) ( − 2 9 − r 2 ) ( − 2 9 − r 3 ) ( − 2 9 − r 4 ) = = ( − 2 9 ) 4 + 7 ( − 2 9 ) 3 − 2 ( − 2 9 ) 2 + 3 ( − 2 9 ) + 1 7 = 5 3 4 8 0 6 .